Islamic Public Finance: How It Matters for Achieving SDGs - Abdul Ghafar Ismail; Nur Hannani Abdul Ghafar; Nurdiyana Sabrina Binti Abdul Rahman (European Journal of Islamic Finance, 2025)
The Sustainable Development Goals (SDGs) agenda is an important global agenda. Public finance, including Islamic public finance, is an essential financial agenda of a country, specifically for Islamic countries. However, both work towards the good welfare of people globally (via SDGs) and the country's people (via Islamic public finance). As both works parallelly, Islamic public finance plays a significant role in advancing SDGs through its unique principles and practices that emphasise social responsibility, ethical investments, and people's welfare. This is where this study aims to highlight the contribution of Islamic public finance towards sustainable development and stimulate discussion on the role of the Baitulmal authorities in the design and implementation of the SDGs. This study uses the narrative review and mapping method. The narrative review is done on past studies or articles on Islamic public finance instruments.  The mapping method identifies the motives of each Islamic public finance instrument and then links them to each goal of the SDGs.  The results show a gap in Islamic public finance elements in the current public finance practice. These few missing elements of Islamic public finance should be regarded as added value elements in the current practice of public finance that widen the scope, generating more revenues in public finance. With more sources of revenue in public finance, more funds could be spent on achieving the SDGs. Hence, the public finance policy is suggested to be constructed by adding the Islamic public finance elements, specifically for Islamic countries.